P4 Using provider training and electronic screening and feedback to improve preventive care for adolescents in primary care. (18th November 2019) - McCarty, CA; Richardson, LP; Parker, E; Stepanchak, M; Stout, J
Abstract : Aims: Emerging evidence suggests that the consistency of provider counseling can be increased through training and the use of screening tools; yet, we know little about the downstream effect on adolescents' sense of control over their health and on their risk behaviors. This study aimed to test whether primary care provider (PCP) training on motivational interviewing together with implementation of an electronic screening and feedback tool would impact provider counseling on health risks and adolescent risk behaviors. Methods: We used a stepped wedge study design and recruited adolescents aged 13-18 from 6 clinics. In the control period, 135 youth received their usual primary care appointment. In the intervention period, 167 youth received an electronic screening and feedback tool prior to their visit, with results sent to the PCP. In between the control and intervention periods, PCPs participated in an online interactive training demonstrating motivational interviewing skills using video-based scenarios, and met to discuss clinic-level reports summarizing adolescent-reported receipt of counseling. Youth were surveyed at baseline and three months about their health risk behaviors, and following the well-child visit regarding the receipt of counseling. We calculated the total number of behaviors counseled on divided by the total number of risk behaviors endorsed and compared across groups using chi-squared analyses. An adjusted linear mixed model was conducted to examine whether the intervention was associated with changes in the mean risk score at the 3-month assessment, adjusting for clinic, age, gender, and baseline risk. Results: Control group participants reported receiving counseling on 35% of moderate risk behaviors compared to 43% of behaviors for intervention participants ( p =0.009). Likewise, adolescents reported receiving counseling on 23% of high risk behaviors in the control group compared to 36% of behaviors in the treatment group ( p <0.001). The linear mixed model indicted that the intervention was associated with a 0.64 greater reduction in overall risk score at 3-month follow up, relative to the control group (95% CI:-1.03, -0.24; p =0.002). Conclusion: Results show promise for electronic screening and feedback and brief provider training to improve the quality and results of healthcare to adolescent patients in primary care settings.